Jumlah Bakteri pada Luka Diabetik Kronik yang Dicuci Menggunakan Ekstrak Air Daun Jambu Biji (Psidium Guava) - Fahni Haris (Alma Ata University Press, 2017)
Various solutions have been recommended for cleanse the wound, however normal saline is favored. Aqueous guava leaf extracts have material that known for antibacterial in the diabetic wound care especially for cleansing. Guava leaf available in Indonesia, but there is unresolved debate about its use. This study use quasi-experimental with pre-test post-test design. Sample in this study consist 19 outpatients who had diabetic chronic wounds care in clinic Kitamura, Pontianak. Analysis of quantitative data was tested with non-parametric analysis, Wilcoxon test and Mann Whitney test to determine the effect of aqueous guava leaves extract in reducing bacterial. Results sowed that he number of bacteria colonies after cleansing the wound using aqueous guava leaves extract was decreased. P-value on first day until seventh day for 10% aqueous guava leaves was p=0.008 (p0.05), but 20% aqueous guava leaves extract most effective than 10% aqueous guava leaves extract.